Trypan blue-assisted iris cyst excision - Alfredo Borgia; Matteo Airaldi; Francesco Semeraro; Sanjay V. Patel; Vito Romano (American Journal of Ophthalmology Case Reports)
Purpose: To describe a novel surgical technique using trypan blue assistance for iris cyst excision. Methods: With viscoelastic in the anterior chamber, the cyst contents are aspirated with a 27G needle. Trypan blue is then injected into the residual cyst cavity to stain its walls. Forceps and anterior vitrectomy are utilized to ensure complete removal of the cyst wall with a safe margin of surrounding iris tissue. Results: The trypan blue-assisted technique facilitates cyst visualization, enabling precise and complete cyst removal. Conclusions: Trypan blue-assisted excision provides an effective approach for iris stromal cyst removal, minimizing recurrence risk and enhancing surgical precision.